2009
DOI: 10.1016/j.it.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Thymic involution and immune reconstitution

Abstract: Chronic thymus involution associated with aging results in less efficient T-cell development and decreased emigration of naïve T cells to the periphery. Thymic decline in the aged is linked to increased morbidity and mortality in a wide range of clinical settings. Negative consequences of these effects on global health make it of paramount importance to understand the mechanisms driving thymic involution and homeostatic processes across the lifespan. There is growing evidence that thymus tissue is plastic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
357
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(380 citation statements)
references
References 80 publications
12
357
1
10
Order By: Relevance
“…Similar observations were made in rodents where studies showed that gonadectomy and the ablation of sex steroids in young male and female rodents increases the production of new naïve T cells by the thymus (Lynch et al 2009;Perisic et al 2010). Although the difference was not statistically significant, we noted a small decrease in inflammatory cytokine production by T cells from ovx adult female rhesus macaques, which is also consistent with the notion that ablation of sex steroids can rejuvenate the immune system in young animals (Holland and van den Brink 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Similar observations were made in rodents where studies showed that gonadectomy and the ablation of sex steroids in young male and female rodents increases the production of new naïve T cells by the thymus (Lynch et al 2009;Perisic et al 2010). Although the difference was not statistically significant, we noted a small decrease in inflammatory cytokine production by T cells from ovx adult female rhesus macaques, which is also consistent with the notion that ablation of sex steroids can rejuvenate the immune system in young animals (Holland and van den Brink 2009).…”
Section: Discussionsupporting
confidence: 91%
“…ATI is a common and well-known feature in various fungal Mendes-Giannini et al 2008;Souto et al 2003), viral (Duan et al 2015;Falkenberg et al 2014;Gao et al 2015) and bacterial infectious diseases (LeyvaRangel et al 2015;Ross et al 2012;Savino 2006). ATI can also be caused by immune suppression (Billard et al 2011;Zhou et al 2016), hunger (Gavia-García et al 2015;Savino et al 2007), chemotherapy, radiography (DeBo et al 2015;Lynch et al 2009), pregnancy (Ekin et al 2016;Jacques et al 2014Jacques et al , 2015, transplant rejection (Gracia-Ahufinger et al 2015;Krenzien et al 2015) and other severe disease conditions (Wang et al 2016). ATI in certain physiological conditions (e.g., during malnutrition and pregnancy) is usually mediated by the neuroendocrine system, and the transient thymic regression is characterized by increased thymocyte death, with the capability to recuperate after the removal of the insult (Gruver and Sempowski 2008;Shanley et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During age-related atrophy, thymic function is mainly affected by changes in the histological structure of the organ including expansion of the perivascular spaces and an increase in the adipose tissue. These changes lead to enhanced vulnerability to autoimmune diseases, infections and cancer in older individuals (Lynch et al 2009). Various molecular and signaling pathways are involved in ATI depending upon the type and strain of infectious agent/s (viral, parasitic, fungal, bacterial) that are involved in pathogenesis (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition for being the key site of T lymphopoiesis in jawed vertebrates, the thymus maintains a competent peripheral T‐cell pool with a broad spectrum of TCR specificities (Lynch et al ., 2009). It is, however, well established that immunity declines with ageing owing to two key factors impeding thymic function: a defect in the survival/proliferation ability of the prethymic hematopoietic progenitor pool coupled to the precocious loss of TECs (Boehm & Swann, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, well established that immunity declines with ageing owing to two key factors impeding thymic function: a defect in the survival/proliferation ability of the prethymic hematopoietic progenitor pool coupled to the precocious loss of TECs (Boehm & Swann, 2013). These age‐related changes, collectively known as thymic involution, represent major driving forces for homeostatic expansion of preexisting peripheral T cells (Lynch et al ., 2009). The net outcome culminates in TCR repertoire skewing with a noticeable increase in the number of effector/memory T cells (Zanni et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%